Survei Resistivitas untuk Menentukan Distribusi Tahanan Jenis Batuan Bawah Permukaan Cekungan Daerah Sedimentasi Kuwu - Yuana, Taufiq; Yulianto, Gatot (BERKALA FISIKA, 2006)
Geophysical survey with resistivity method has been done in Bledug area, Kuwu, Grobogan, Central Java which have geology or geophysic phenomena mud blast or mud volcano. The principle resistivity method is measurement resistivity of rock by conducting current and also measure potential difference.This survey using NANIURA Resistivitymeter Model NRD 22S. Resistivity measurement has  been done sounding with schlumberger configuration. The result 3 sounding point, northside, southside and among bledug area. Data processing using IPI version 6.0 for windows program. The result of data processing is thickness and rock resistivity. Final interpretation made with combining sounding data and geology data so that subsurface picture of resistivity distribution. The result of final interpretation shown  bledug area and surrounding is thicknesses which have a distribution resistivity of rock  has the range 0,1-1 Ωm. The conclusion that survey area is flake from salt dome.     Keywords: Bledug Kuwu, resistivity method, mud vulcano